Isis in Afghanistan - Quraishi, Najibullah
ISIS's rapid expansion across Iraq and Syria in 2014 shocked the world. Now in 2015, the self -proclaimed Islamic State in on the rise in Afghanistan. FRONTLINE reveals the degree to which ISIS in gaining a foothold in the country, and how they're focusing their efforts on training a new generation of Jihadists: children as young as three.
In English with optional English subtitles.
Keywords: IS (Organization); Terrorism -- Afghanistan; Terrorism -- Pakistan